PENGARUH JENIS PENGEMAS TERHADAP NILAI TAMBAH BIJI KAKAO FERMENTASI SELAMA PENYIMPANAN - Purwaningsih; Tri Marwati; Titiek F. Djaafar (Program Studi Agroteknologi INSTIPER, 2019)
Cocoa is a leading commodity in the Special Region of Yogyakarta that needs to be developed. In Nglanggeran, Patuk, Gunungkidul, stands the Agricultural Technology Park (ATP) based on cocoa comodities that needs to be supported by postharvest technology studies including packaging and storage of cocoa beans to be able to produce quality and safe processed chocolate. The purpose of this study is to find out added value of cocoa beans with and without the addition of Lactobacillus plantarum HL 15 starter and packaging during storage. This research was conducted in January - December 2018 in the Ngudi Raharjo II Farmer Group, Plosokerep, Patuk, Gunung Kidul. The experimental design used was factorial completely randomized design 2 replications, with the first factor being the type of fermented cocoa beans (B), consisting of: fermented cocoa beans with starter L. plantarum HL. 15 (B1) and fermented cocoa beans by farmers (without starter) (B2) and the second factor type of packaging (K), consisting of: PP plastic in vacuum (K1), PP plastic without vacuum (K2) Plastic container (K3), PP plastic + vacuum + plastic container (K4). Nylon sack (farmer control) (K5). The result is an increase in added value from the highest to the lowest is IDR 2,675/kg (K4B1), IDR 2,375/kg (K2B1), IDR 2,025/kg (K1B1), IDR 1,725 /kg (K3B1), IDR 1,350/kg (K3B2) , Rp. 1,100 /kg (K2B2) and (K1B2), Rp. 1,050/kg (K2B2), Rp. 475/kg (K5B1), and Rp. 100/kg (K5B2). Keywords: fermented cocoa beans, added value, packaging